Bahasa Inggris - M. Miftach Fakhri; Della Fadhilatunisa; Yuanita B; Nur Rahmah Sari; Rosidah (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2022)
A good accountant is the one who is able to do the preparation of financial statements. In addition, akuntan must gain an understanding of the financial reporting framework and significant accounting policies intended for use in the preparation of financial statements. Optimization of the preparation of financial statements that have been described above can be further realized by using software in the preparation of financial statements. One application or software that can be used in the preparation of financial statements is "Zahir Accounting". The purpose of the study was to find out the user's perspective on the zahir accounting application with the extended technology acceptance model (ETAM). The population in this study were Trainees in The Preparation of Financial Statements with the Zahir Accounting Application. The research had five main topics: perceived ease of use, usefulness, trust, enjoyment, behavioral intention. The data collection technique is a questionnaire through a google form. Data analysis using the Smart PLS application by hypothesis testing, namely structural models or inner models. The results showed that all eight hypotheses were accepted with positive effect results, but hypotheses 5 and 7 had no significant effect